Geographical and temporal differences in gastric and oesophageal cancer registration by subsite and morphology in Europe - Giusti, Francesco; Martos, Carmen; Bettio, Manola; Negrão Carvalho, Raquel; Zorzi, Manuel; Guzzinati, Stefano; Rugge, Massimo (Frontiers in Oncology, 2024)
Gastric and oesophageal cancers pose a serious public health concern. In 2020 a total of 189,031 incident cases (136,038 stomach, 52,993 oesophagus) and 142,508 deaths (96,997 stomach, 45,511 oesophagus) were estimated in Europe. Oesophago-gastric cancers are a heterogeneous disease, with different aetiology and epidemiology for the various topographic subsites and main histopathological types. Topography subsite and morphology is key information to allow differentiating oesophagogastric cancers. Correct registration and coding of such variables are fundamental in allowing proper description of the epidemiology of different subsites and histopathological types of oesophago-gastric cancers. The aim of this article is to highlight geographical and temporal variability in topography and morphology of oesophago-gastric cancers observed in Europe in the considered period.Methods: Data collected in the framework of the ENCR-JRC (European Commission's Joint Research Centre) data call and feeding the European Cancer Information System (ECIS) were used to assess the variability of topography and morphology registration of gastric and oesophageal cancer in Europe in the period 1995-2014. Malignant cancers of the stomach and the oesophagus were selected following, respectively, topography codes C16 and C15 of the International Classification of Diseases for Oncology, third edition (ICD-O-3). Analyses were performed by subsite, morphology group, year, sex, and European region.Results: A total of 840,464 incident cases occurring in the period 1995-2014 -579,264 gastric (67.2%) and 276,260 (32.8%) oesophageal carcinomaswas selected for the analysis. Data was recorded by 53 PBCRs (9 based in Northern Europe, 14 in Western Europe, 3 in Eastern Europe and 27 in Southern Europe) from 19 countries. Conclusion: A wide variability in oesophago-gastric cancers topographic subsites and histopathological types patterns was observed, with a corresponding improvement in accuracy of registration in the analysis period. PBCRs are ideally placed to guide the epidemiological evaluations of such a complex group of diseases, in collaboration with clinicians, patients and other public health stakeholders.